A Novel Polyacrylamide Magnetic Nanoparticle Contrast Agent for Molecular Imaging using MRI - Bradford A. Moffat; G. Ramachandra Reddy; Patrick McConville; Daniel E. Hall; Thomas L. Chenevert; Raoul R. Kopelman; Martin Philbert; Ralph Weissleder; Alnawaz Rehemtulla; Brian D. Ross (Molecular Imaging)
A novel Polyacrylamide superparamagnetic iron oxide nanoparticle platform is described which has been synthetically prepared such that multiple crystals of iron oxide are encapsulated within a single Polyacrylamide matrix ( P oly A crylamide M agnetic [PAM] nanoparticles). This formulation provides for an extremely large T 2 and T 2 * relaxivity of between 620 and 1140 sec −1 mM −1 . Administration of PAM nanoparticles into rats bearing orthotopic 9L gliomas allowed quantitative pharmacokinetic analysis of the uptake of nanoparticles in the vasculature, brain, and glioma. Addition of polyethylene glycol of varying sizes (0.6, 2, and 10 kDa) to the surface of the PAM nanoparticles resulted in an increase in plasma half-life and affected tumor uptake and retention of the nanoparticles as quantified by changes in tissue contrast using MRI. The flexible formulation of these nanoparticles suggests that future modifications could be accomplished allowing for their use as a targeted molecular imaging contrast agent and/or therapeutic platform for multiple indications.